Aerobic training in myotonia congenita: Effect on myotonia and fitness. Issue 4 (23rd March 2017) - Andersen, Grete; Løkken, Nicoline; Vissing, John
ABSTRACT: Introduction: Exercise has not been investigated in myotonia congenita (MC). We investigated whether regular aerobic training can reduce myotonia and improve fitness. Methods: Untrained patients with MC (age: 24–62 years; n = 6) completed 28 ± 3 sessions of 30‐minute cycle ergometer training at 75% of maximal capacity for 11 ± 1 weeks. Fitness was evaluated by maximal oxygen uptake. The level of myotonia was assessed by the Myotonia Behavior Scale, 14 step stair test, timed up and go test, and hand and eye closure‐open tests. Results: Training increased fitness by 9% (95% confidence interval [CI], 1–17%; P = 0.02) and maximal workload by 10% (95% CI, 3–18%; P = 0.03). None of the myotonia tests changed in a clinically meaningful way. Conclusions: Regular endurance training improves fitness and maximal workload performance in patients with MC. The lack of creatine kinase elevations indicates that muscle damage did not occur. Improved fitness, however, did not change myotonic symptoms in this small cohort. Muscle Nerve 56 : 696–699, 2017